QUALITY OF Hovenia dulcis Thunb. ROUND FENCE POSTS SUBMITTED TO PRESERVATIVE TREATMENT - Silveira, Amanda Grassmann da; Baldin, Talita; Vidrano, Bibiana Regina Argenta; Santini, Elio José; Trevisan, Rômulo; Talgatti, Maiara (Floresta, 2018)
This study aimed to test the hypothesis regarding the quality of Hovenia dulcis fence posts, which states that it varies according to the treatment period when subjected to the sap displacement method.. The experiment began with 15 round fence posts distributed vertically in tank containing copper sulfate, sodium dichromate and boric acid (CCB) solution at 2.5% concentration. In order to verify the influence of time on the efficiency of the method, the posts stayed in the preservative solution for periods of 3, 6, 9, 12 and 15 days, which were assessed. Penetration and retention in three positions were analyzed, which corresponded to the regions of base, middle and top parts. With regards to treated wood, samples of each piece were prepared for testing in field test. Then, weight loss and bending properties were assessed. According to the results of penetration and retention, wood treated on the period of 15 days is the only one that can be used directly with the soil. After assessment of the weight loss, the periods of 12 and 15 days of treatment increased the classification of wood from moderately to strong resistant. The bending test showed significant reduction in rigidity and strength of the material, even in the treated ones, which demonstrates that the forest environment in which samples were exposed promoted the process of wood decomposition.